A young woman with multiple soft tissue tumors in various parts of the body, (Extra Abdominal Fibromatosis and Lymphangioma in both Axillas) - Kalam, MD A; Ahmad, F; Hassan, M; Nasiruddin, Md; Rahman, SA; Rahman, M; Islam, Farhana (Bangladesh Journal of Plastic Surgery, 2010)
The term fibromatosis refers to a group of benign soft tissue tumors (fibromas), which have certain characteristics in common, including absence of cytologic and clinical malignant features, a histology consistent with proliferation of well-differentiated fibroblasts, an infiltrative growth pattern, and aggressive clinical behavior with frequent local recurrence. Lymphangiomas are malformations of the lymphatic system, which is the network of vessels responsible for returning to the venous system of excess fluid from tissues. Here we report a case of 30 years old lady with history of multiple soft tissue tumours in thigh, axilla and abdomen. On physical examination the swelling of the thigh and abdomen were firm and those of axilla were soft. All the tumours were excised surgically and diagnosis of thigh swelling was fibromatosis and that of axilla was lymphangioma, on histopathology. DOI: http://dx.doi.org/10.3329/bdjps.v1i1.6490 Bangladesh Journal of Plastic Surgery (2010) Vol. 1 (1) pp.29-32